Knowledge, attitude and self-efficacy in the written expression of students with Learning Disabilities - Κ. Δημάκος, Ιωάννης; Χέλμη, Μαργαρίτα (Psychology: the Journal of the Hellenic Psychological Society, 2020)
Abstract is available in the PDF